Artificial Intelligence As an Object of Intellectual Property (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The level of development of artificial intelligence can be discussed only conditionally, because its development is accelerating, and new things are quickly becoming obsolete every second. This is especially evident in the fastest growing field of artificial intelligence - artificial neural networks. By the beginning of 2023, ChatGPT, DALL-ye and other multimodal neural networks, their intellectual capabilities are improving by increasing the number of parameters (accepted methods, including those that are not available to humans), as well as by using them. Large amounts of training data that humans cannot physically process have raised the issue of creating wired artificial intelligence. For example, multimodal generative models of neural networks can create pictures, literary and scientific texts in such a way that it is not always possible to distinguish whether they were created by a human or an artificial intelligence system.